Strategi Unit School of Enabler and Corporate Transformation Dalam Meningkatkan Pemahaman Komunikasi Di Telkom Corporate University - Arfiati, Iin; Ika Sartika (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
The development of information and communication technology in the Society 5.0 era has a significant impact on various aspects of life, including in the world of education and communication. One of the innovations in the learning process is the use of video learning as an interactive and flexible educational media. This study aims to explain the strategies used by the SoECT (School of Enabler & Corporate Transformation) unit in video learning human representation, identify factors that influence its success, and analyze the effect of the implementation of these strategies on improving employee communication understanding at Telkom Corporate University. This research uses a mixed method approach, with descriptive qualitative and inferential quantitative methods. The results showed that the effectively designed video learning strategy was able to significantly improve communication understanding. This is proven through statistical tests, where a correlation coefficient value of 0.721 and significance <0.001 are obtained, as well as a determination value of 51.9%, which indicates a strong relationship between the video learning strategy and employee communication understanding. Thus, the SoECT unit's strategy in preparing video learning is not only effective in delivering information, but also has a long-term impact on improving the quality of communication within Telkom Corporate University.